The Goddess of Warsaw : a novel - Barr, Lisa (Harper, an imprint of HarperCollinsPublishers, 2024)
"From the New York Times bestselling author of Woman on Fire, the harrowing and ultimately triumphant tale of a Jewish WWII assassin turned Hollywood star. In 2005, Siena Hayes is Hollywood's latest It Girl, but she has her sights set higher than the screen, she wants to be behind the camera. So when Siena meets Lena Browning, the enormously mysterious and famous actor from decades past, Siena sees her big break. Siena wants to direct Lena's biopic-but Lena's past may turn out to be more than Siena bargained for. Before she was a "Living Legend," Lena Browning was Bina Blonski, a member of Warsaw's Jewish elite whose life and family were destroyed by the Nazis. In 1943, in the ghettos of Warsaw, Bina lives with her husband, Jakub. Determined to fight back against Nazi rule, beautiful, blonde Bina acts as a spy on the Aryan side fearlessly protecting the remaining Warsaw Jews, gaining intel, and stealing weapons. Along the way, her feelings grow more complicated as she falls in love with Aleksander, an ally to her in resistance . . . and Jakub's brother. But the cause prevails-and Lena accomplishes amazing feats of bravery, though she can't help but sacrifice so much in the process . . . Over a decade after escaping the ghetto, Bina, who now goes by Lena, has risen to fame in Hollywood. She sees her old life at every turn and hungers for revenge against the Nazis who are still everywhere around her. This is Lena's chance to right the past's wrongs and perhaps even find the happy ending she never had"--